Covid-19 Mitigation Strategy in Higher Education Institutions: A Qualitative Study at Indonesian Immigration and Correctional Science Colleges - Asep Kurnia; Vita Nurul Fathya (Jurnal Ilmiah Kebijakan Hukum, 2022)
Covid-19 Pandemic is a global issue affecting higher education institutions, including colleges for future government officials like the Polytechnics of Correctional Science and the Polytechnics of Immigration. To present a research article regarding this issue, the qualitative method and the interview technique were used for this purpose. The data were collected based on interviews with actors involved in mitigating Covid-19 in those Polytechnics. As the result of interviews, several strategies for Covid-19 mitigation are obtained. They include strengthening the role of leadership in finding solutions in uncertain conditions, campus zoning, providing quarantine and self-isolating facilities, conducting tracing, testing, treatment, and other health protocols. In addition, the Covid-19 mitigation strategies also include implementing virtual learning methods during pandemics and providing access to anti-virus medicines, vitamins, and other kinds of supplements for employees and students. The campus management also conducts mitigation strategies by accompanying students during isolation, educating students and staff about self-protection from the virus, establishing a campus task force to organize mitigation activities, and also conducting coordination with other stakeholders. Overall, the research shows that the Covid-19 mitigation strategy in Poltekim and Poltekip campuses is quite effective. However, improvements in several areas are needed in the future. Regarding the strategy for Covid-19 mitigation in higher education institutions, the authors recommend several proper prevention strategies such as increasing the number of rooms and facilities to accommodate classes with health protocols and agreeing on a common perception among stakeholders about the learning, coaching, and methods of treatment in these colleges.